2022
DOI: 10.3390/biology11020178
|View full text |Cite
|
Sign up to set email alerts
|

Viral and Host Genetic and Epigenetic Biomarkers Related to SARS-CoV-2 Cell Entry, Infection Rate, and Disease Severity

Abstract: The rapid spread of COVID-19 outbreak lead to a global pandemic declared in March 2020. The common features of corona virus family helped to resolve structural characteristics and entry mechanism of SARS-CoV-2. However, rapid mutagenesis leads to the emergence of new strains that may have different reproduction rates or infectivity and may impact the course and severity of the disease. Host related factors may also play a role in the susceptibility for infection as well as the severity and outcomes of the COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…The few virions that establish infection and the low probability of variant transmission during acute infection [2, 12, 13], especially for Omicron with its shorter serial interval [14], still give rise to large clone sizes as observed here. Many of those variants will die out, because those individuals have low contact rates, or host gene variants may reduce cellular entry and viral replication [15], or the variant is less fit. Expansion of some clones is likely due to a combination of super-spreader events and variant fitness [16], an investigation of which would require further epidemiological and genetic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The few virions that establish infection and the low probability of variant transmission during acute infection [2, 12, 13], especially for Omicron with its shorter serial interval [14], still give rise to large clone sizes as observed here. Many of those variants will die out, because those individuals have low contact rates, or host gene variants may reduce cellular entry and viral replication [15], or the variant is less fit. Expansion of some clones is likely due to a combination of super-spreader events and variant fitness [16], an investigation of which would require further epidemiological and genetic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of changes in IFN-λ3 during the course of COVID-19 revealed that patients transitioning from mild to severe disease show a characteristic peak value a few days before the transition (9). The change is (P4) (15). Single nucleotide polymorphisms (SNPs) in ACE2 and TMPRSS2 might contribute to selective binding of SARS-CoV-2.…”
Section: Interferon-lambda 3 (Ifn-λ3)mentioning
confidence: 99%
“…Conversely, viruses can regulate host miRNA to suppress the host im mu ne sy st em . Prev ious s tu dies hav e id en t i fi e d differentially expressed miRNAs in COVID-19 patients through transcriptome analysis (1)(2)(3)(4)(5). In particular, virus RNA can play as sponge of host miRNA to regulate immune processes.…”
Section: Introductionmentioning
confidence: 99%